Autonomic and verbal responses to the experimental nociceptive stimulation - Opavský, Jaroslav; Dostálek, M; Maráček, Radomír (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1991)
Human pain studies require a multidimensional evaluation for the complex understanding of the stated problem. For this reason, not only the subjective verbal evaluations but also objective indices are considered. To estimate the latter ones, autonomic, vasomotor and electrodermal responses to electric stimulation were selected in the presented study together with the verbal assessment. In comparison with the chronic non-malignant pain patients, different findings were obtained in healthy subjects, both in the objective and subjective indices. In the second part of the study, the analgesic effects of acetylsalicylic acid or codeine or placebo were compared under indentical experimental conditions. The differences were less impressive than those found in the first part of the study. The antinociceptive effect was registered only after codeine administration.
Keywords: kodein; lidé; Adult; dospělí; verbální chování; Pain Measurement; Reference Values; Back Pain; Skin; Codeine; Autonomic Nervous System; autonomní nervový systém; Male; Verbal Behavior; referenční hodnoty; Humans; Pain; mužské pohlaví; měření bolesti; Aspirin; bolesti zad; kůže; bolest; elektromyografie; Electromyography